Skladenjske razlike v katekizmih slovenskih in hrvaških reformatorjev (Trubar 1550, Konzul 1564; Krelj 1566, Vlačić 1566) - Orel, Irena (Slavia Centralis, 2020)
Syntactical differences in the catechisms of Slovenian (Trubar 1550; Krelj 1566) and Croatian (Konzul 1564; Flacius 1566) reformers The article presents linguistic differences on syntactic levels in selected and essentially identical Slovenian and Croatian translations of texts from 16th Century catechisms: from the sermon of faith in Primož Trubar’s Catechism (1550) and the Croatian-Latin edition by Štefan Konzul (1564) as well as the Carniolan and Croatian translation (allegedly by Matthias Flacius Illyricus) of the school catechism by Sebastijan Krelj in the Children’s Bible (Otročja biblija) (1566). The hypothesis to be verified is whether the Croatian texts, despite the possible influence of the Slovenian version on them, do not contain (as many) Germanic syntactic structures as the Slovene texts.